2020
DOI: 10.9734/jeai/2020/v42i230473
|View full text |Cite
|
Sign up to set email alerts
|

Genotype x Environment Interactions in Sugarcane under Irrigation for Agronomic Traits at Advanced Screening Stage in Ferké, Northern Ivory Coast

Abstract: Background:The selection procedure of commercial sugarcane varieties introduced in Ivory Coast involves two different stages. Four varieties pre-selected at the first stage regarding a previous trial were due to be tested at the advanced stage. Aims: The study aimed to determine the best performing sugarcane genotypes at the advanced selection stage under sprinkler irrigation, in comparison with to two check varieties (R579, SP70-1006). Methodology: The same field experiment was carried out on two different lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…These findings are in accordance with those of Péné and Déa, (2000) and Péné et al, (2012) in their studies which indicated that varietal selection appears to be an essential component in increasing sugarcane productivity in same way as irrigation. Péné and Béhou (in 2019) in Côte d'Ivoire, with exception of yield. However, we note a difference in yield between varieties evaluated in general.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in accordance with those of Péné and Déa, (2000) and Péné et al, (2012) in their studies which indicated that varietal selection appears to be an essential component in increasing sugarcane productivity in same way as irrigation. Péné and Béhou (in 2019) in Côte d'Ivoire, with exception of yield. However, we note a difference in yield between varieties evaluated in general.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of broad-sense heritability (h²) are categorized according to Robinson [30] cited by different authors [25,31,38,42] as low (<30%), moderate (30≤-<60%) or high (≥60%).…”
Section: F) Determination Of Genetic Parametersmentioning
confidence: 99%
“…Heritability represents the relative importance of genetic and environment factors in the expression of phenotypic and genotypic differences among genotypes within a population [3,6,[28][29][30]. Therefore, the knowledge of heritability related to important traits and the correlations among them are key issues to determine the best selection strategy [31][32]38]. Genotypic coefficient of variation (GCV) is another measure of relative genetic variation of a trait within a population [33].…”
Section: F) Determination Of Genetic Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Mixed models have been applied successfully to animal and plant breeding programs. In the latter case, they are used widely for breeding of perennial plants such as selection of cupuassu clones (Maia et al, 2011), papaya progenies (Pinto et al, 2013), sugarcane (Barreto et al, 2019), and evaluation of genotype-environment interactions in sugarcane (Péné;Béhou, 2020), maize (Dias et al, 2018), among several studies found in the literature. This method is adapted for annual crop breeding only recently, one of the reasons being the experimentation type involved.…”
Section: Introductionmentioning
confidence: 99%